Atopic dermatitis and Valpha24+ natural killer T cells. - Ilhan, Fulya; Kandi, Basak; Akbulut, Handan; Turgut, Dilara; Cicek, Demet (My University, 2007)
OBJECTIVE: Atopic dermatitis is a chronic inflammatory skin disease associated with cutaneous hyperreactivity to environmental triggers and is often the first step in the atopic march that results in asthma and allergic rhinitis. Helper T cells and their cytokines, in addition to IgE and eosinophils, play a major role in the pathogenesis of atopic dermatitis. Natural killer T (NKT) cells may play a role in atopic dermatitis status. METHODS: The authors examined the percentage of Valpha24+CD161+ NKT cells and CD3+CD16+ CD56+ NKT cells in peripheral blood from 23 patients with atopic dermatitis aged 8 to 35 years (mean, 21.77+/-2.88 years) and 30 healthy controls aged 18 to 32 years (mean, 24.32+/-2.44 years) by using flow cytometric analysis. The mean percentages of Valpha24+CD161+ NKT cell subtypes in the atopic dermatitis group and the healthy group were 0.29%+/-0.02% and 0.42%+/-0.05%, respectively (P<.001). RESULTS: Percentages of Valpha24+CD161+ NKT cell subtypes are significantly lower in patients with atopic dermatitis than healthy individuals. On the other hand, the CD3+CD16+CD56+ NKT cell subtype does not differ between the groups. CONCLUSIONS: The reduction of Valpha24+CD161+ NKT cells subtypes may be involved in the immunopathogenesis of atopic dermatitis.
Keywords: Adolescent; Adult; Antigens, CD; Antigens, Surface; Child; Dermatitis, Atopic; Flow Cytometry; Humans; Immunoglobulin E; Killer Cells, Natural; Lectins, C-Type; Receptors, Antigen, T-Cell, alpha-beta; Statistics, Nonparametric; T-Lymphocyte Subsets; CD161 antigen; immunoglobulin E; lectin; leukocyte antigen; lymphocyte antigen receptor; membrane antigen; adolescent; adult; article; atopic dermatitis; blood; child; comparative study; flow cytometry; human; immunology; natural killer cell; nonparametric test; T lymphocyte subpopulation